Transactive energy and peer-to-peer energy trading based on blockchain : A comprehensive review and a generalized cyber-physical framework - Mazrae, Alireza Khanjari; Naderian, Hossein; Baghaee, Hamid Reza; Sheikh-El-Eslami, Mohammad Kazem; Karimi, Mazaher (Elsevier, 2025)
This research comprehensively reviews blockchain-based transactive and peer-to-peer energy trading systems, highlighting their challenges, benefits, and limitations. These systems can revolutionize the energy industry by facilitating decentralized energy transactions and enhancing energy efficiency. The research proposes a general pattern for establishing and operating blockchain-based transactive and peer-to-peer energy trading platforms. It considers critical aspects such as smart contracts, consensus mechanisms, data privacy, and system interoperability. Furthermore, it proposes a generalized framework to serve as a basis for designing and implementing blockchain-based platforms for transactive energy and peer-to-peer energy trading. The framework comprises critical components, including smart contracts, consensus mechanisms, data privacy, and system interoperability. This research provides valuable insights for researchers, policymakers, and industry professionals seeking to understand and develop blockchain-based solutions for transactive and peer-to-peer energy trading.
Keywords: Blockchain; Consensus mechanisms; Data privacy; Peer-to-peer energy trading; Smart-contract; Transactive energy; fi=Sähkötekniikka|en=Electrical Engineering|